Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. The effectiveness of the seven – cycle learning strategy 7E’s on the achievement and attitude towards the course for students of the Curriculum and Teaching Methods course at Shaqra University in the Kingdom of Saudi Arabia Co- Prof. Lafa Mohmmed H. Alotaibi 2. Requirements for activating the digital economy in the education sector in Oman to face challenges and crises – the case of Covid-19 pandemic Mr. Salman Sloum Khamis Alhinai, Co-Prof. Omer Ismail Hamad, Co-Prof. Khalaf Marhoun AlAbri , Prof. Ali Sharaf Al Musawi 3. The Effectiveness of a Training Program Based on the Universal Design for Learning in Improving the Teaching Competencies of Teachers of Students with Learning Difficulties in Al-Ahsa Governorate Mrs. Wijdan Rashid Al-Rasheed, Dr. Tareq Yousef Melhem 4. Employing some Web 2.0 applications in developing the skills of producing digital stories for kindergarten teachers Mrs. Shoq Hasan Al-Sa’ida 5. The Level of Psychological Adjustment Among a Sample of Female Breast Cancer Patients in Riyadh Province and Its Relationship to Self-Esteem Mrs. Eman Mohammad Sharee Al-Otibi 6. Psychometric characteristics for attachment styles among a sample of secondary school students in Buraidah city Mrs. Nafla Sulaiman Al-Qusayer, Prof. Sufyan Ibrahim Al-Rebdi